2018
DOI: 10.1039/c8nr07498d
|View full text |Cite
|
Sign up to set email alerts
|

Interlayer interactions in 2D WS2/MoS2heterostructures monolithically grown byin situphysical vapor deposition

Abstract: MoS2/WS2 2D heterostructures grown by in-situ reactive sputtering deposition exhibit a strong interlayer coupling and associated exciton relaxation at the interface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
62
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 57 publications
7
62
1
1
Order By: Relevance
“…26 The characteristics of van der Waals heterostructures are represented not only by the constituent monolayers but also by the interactions among the layers. Recently, various types of van der Waals heterostructures based on MoS 2 have exhibited several interesting electrical, optical, and magnetic properties, [27][28][29][30][31][32][33][34][35][36][37][38][39] but none has reported the mechanism of interface interactions (vdW heterostructures) between MoS 2 and Si 2 BN. We have chosen a 2D Si 2 BN (ref.…”
Section: Introductionmentioning
confidence: 99%
“…26 The characteristics of van der Waals heterostructures are represented not only by the constituent monolayers but also by the interactions among the layers. Recently, various types of van der Waals heterostructures based on MoS 2 have exhibited several interesting electrical, optical, and magnetic properties, [27][28][29][30][31][32][33][34][35][36][37][38][39] but none has reported the mechanism of interface interactions (vdW heterostructures) between MoS 2 and Si 2 BN. We have chosen a 2D Si 2 BN (ref.…”
Section: Introductionmentioning
confidence: 99%
“…From the results in Figure and , the WF of 3L‐WS 2 /3L‐MoS 2 and 3L‐WS 2 was estimated to be 5.09 and 5.26 eV, respectively. WS 2 /MoS 2 is known to form a so‐called type II heterostructure, as shown in Figure , which can effectively separate electron–hole pairs at the interface . Theoretical calculations showed that the valence band maximum was mainly occupied by the d orbital of W in the WS 2 layer, whereas the conduction band minimum primarily originated from the d orbital of Mo in the MoS 2 layer .…”
Section: Resultsmentioning
confidence: 99%
“…2D atomically thin layered materials, such as transition metal dichalcogenides (TMDs), have attracted growing research attention owing to their rich physics and various device applications . However, the nature of individual 2D materials, such as the zero bandgap of graphene, low carrier mobility of grown TMD, and the rapid degradation of black phosphorus under the atmospheric condition, has hindered the practical application of 2D materials .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations